Evolution Characteristics of China's Big Food Concept Economic Statistics Data Under the Perspective of Food Security - Dafang WU; Quanyan WANG; Shuaishuai JIA (Guangdong nongye kexue)
Food is of paramount importance to the people, and food consumption is the most basic consumption demand. Food safety is an important component of national security. This article analyzes the dynamic evolution characteristics of China's food security security pattern from the perspective of economic statistics. In just 30 years since 1993, the proportion of grain in the production structure of the three major categories of agricultural products (grain, vegetables, and fruits) has decreased from 53.83% to 37.55%. During the same period, the growth rate of animal husbandry meat production and fishery aquatic product production has also been significantly higher than that of grain production. The food consumption structure and grain consumption structure of Chinese residents have undergone fundamental changes. Currently, the proportion of feed grain consumption has exceeded that of food consumption, and China's food security situation has undergone a fundamental reversal. The traditional narrow caliber concept of food security is no longer suitable for management needs, and implementing the big food concept is a feasible solution to better address the challenges of food security. This article analyzes the evolutionary characteristics of China's food economy statistics from the perspectives of production, consumption, and trade, explores the theoretical origins and practical background of transforming the concept of food security, and explores feasible solutions for implementing the concept of big food security and effectively addressing food security challenges. Based on agricultural and related industry statistics, as well as household consumption expenditure surveys, food statistics introduce the data framework of big food economy statistics. Based on agriculture, animal husbandry, and fisheries, food production structure statistics and trend analysis are carried out separately. Based on the food supply balance table, trend analysis of changes in the supply and demand of staple foods is conducted. Research has found that China's agricultural production structure has undergone significant changes, with a decrease in the proportion of grain production in the three major categories of agricultural products; The proportion of grain in residents' food consumption structure has decreased, and the rapid development of animal husbandry and fishery production has led to an increase in the proportion of feed grain consumption. The security of feed grain supply has become the main contradiction in maintaining China's food security; China's soybean supply heavily relies on imports, posing a potential threat to the healthy development of animal husbandry and fisheries, and posing significant risks to food security. Based on this, it is believed that actively implementing the concept of big food is an effective solution to address the current challenges of food security; We can reduce the demand for feed grains by raising livestock with straw, developing the forage industry, developing agroforestry for planting forage and breeding livestock, building offshore pastures, and developing marine fisheries; We can build a diversified food supply system and meet residents' food consumption and nutritional security needs through active development of facility agriculture, biological agriculture, and edible mushroom industry.